Concentration of radiocaesium in rice and irrigation water, and soil management practices in Oguni, Date, Fukushima. (October 2016) - Tsukada, Hirofumi; Ohse, Kenji
ABSTRACT: The concentration of radiocaesium ( 134 Cs and 137 Cs) in brown rice collected from Oguni, Date, Fukushima in 2011 was over 500 Bq kg −1, which was the provisional regulation value in 2011, and rice cultivation was prohibited in 2012. Rice culture was resumed following the application of K fertilizer as a countermeasure in 2013. The concentration of 137 Cs in soils and irrigation water in 2013 was in the range of 1200 to 4000 Bq kg −1 ( n = 31) and 0.078 to 1.1 Bq L −1 ( n = 7), respectively. The concentration of 137 Cs in the dissolved fraction in irrigation water filtered with 0.45 µm pore‐size membrane filter was a relatively constant at 0.019 to 0.038 Bq L −1 ( n = 7). The concentration of 137 Cs in brown rice cultivated in the paddy fields after implementing the countermeasure was 1.1 to 24 Bq kg −1 dry weight ( n = 29), which was lower than the Standard Limits (100 Bq kg −1 ). However, the concentration of Cs in rice cultivated under a similar agricultural management as in 2011 and prior to the Tokyo Electric Power Company Holdings' (TEPCO) Fukushima accident was over the Standard Limits. Integr Environ Assess Manag 2016;12:659–661. © 2016 SETAC Key Points: Application of potassium fertilizer effectively lowered the concentration of radiocaesium in brown rice, cultivated in Oguni, Fukushima in 2013, to levels that were below the Standard Limits (100 Bq kg −1 ). The concentration of radiocaesium in brown rice cultivated without application of potassium fertilizer in Oguni was over the Standard Limits. The uptake of 137 Cs by rice plants from irrigation water in Oguni, including the dissolved and suspended matter fractions, was very limited.